Implementasi Program Tahfidz Juz 30 dalam Meningkatkan Kemampuan Hafalan Peserta Didik di MTs Al-Qodiri 4 Tahun Pelajaran 2025/2026 - Rehanuddin Aji Saputra; Fikri Farikhin (EduInovasi: Journal of Basic Educational Studies, 2026)
The Al-Qur'an tahfidz program in madrasah is a strategic instrument for strengthening character education and religious competence in the digital era. However, its implementation often faces practical obstacles such as inconsistency in muroja'ah (reviewing memorization) and differences in students' basic abilities. This qualitative case study research aims to comprehensively describe and analyze the implementation process of the juz 30 tahfidz program and its impact on improving memorization skills and character building of students at MTs Al-Qodiri 4 for the 2025/2026 Academic Year. Data collection was conducted through semi-structured interviews, participatory observation, and documentation. Data validity was tested using source and method triangulation, then structurally analyzed using an interactive model encompassing data reduction, data display, and drawing conclusions. The research findings indicate that the implementation of the tahfidz program is carried out through a systematic process integrated into the curriculum as a flagship program. Operationally, the learning relies on discipline and religious habituation through the application of talaqqi, takrir, and muroja'ah methods. To overcome various obstacles in the field, the quality of memorization is strictly controlled through a multi-layered evaluation process (daily, weekly, and monthly). This series of processes provides a holistic impact; cognitively, it impacts the improvement of fluency and makhraj (pronunciation) accuracy of the juz 30 memorization. Affectively and spiritually, this program has a transformative impact on increasing discipline, responsibility, the formation of Islamic etiquette (adab), and the creation of a solid Qur'anic culture in the madrasah environment.